A study on chikungunya outbreak during 2007 in Kerala, south India - M. Kannan, R. Rajendran, I.P. Sunish, R. Balasubramaniam, N. Arunachalam, R. Paramasivan, S.C. TewariP. Philip Samuel & B.K. Tyagi (Indian J Med Res 129, March 2009, pp 311-315, 2009)
Interpretation & conclusions: Chikungunya invaded Kerala State for the first time in 2006 and continues to be a major vector borne disease in the State. The clinical symptoms in affected cases highlighted high fever, sever myalgia and prolonged arthralgia, with occasional history of skin itch/rash (petechiae).